From traditional to digital media: Sources of information and resistance behavior of COVID-19 vaccination - Illahi, Azizun Kurnia; Wardasari, Nilam; Laturrakhmi, Yun Fitrahyati (Jurnal Komunikasi, 2025)
The study aims to map rural communities’ attitudes and acceptance of the COVID-19 vaccine, examine the sources of information they rely on, and analyze the communication networks formed among vaccine-resistant groups. Findings reveal a balance between digital and conventional information sources in accessing COVID-19-related information, supported by sufficient human resources and infrastructure in certain areas. Social media and television emerge as the dominant sources of vaccine-related information, indicating high exposure to media content. Meanwhile, healthcare workers, health cadres, and government institutions serve as secondary sources of information. Notably, word-of-mouth remains a significant channel for spreading misinformation, contributing to high acceptance of hoax messages and reinforcing vaccine resistance within the rural community of Tawangsari.